2015
DOI: 10.1177/0009922815596070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Information Technology Tools to Support the Asthma Medical Home

Abstract: This study aimed to evaluate the impact of information technology tools on the outcomes of children with asthma in the medical home. A registry was established for children aged 4 to 18 years with an ICD-9 code for asthma. Changes to the electronic health record included modifications to notes, care plans, and orders. A retrospective analysis of emergency department and in-patient utilization for a cohort of patients was conducted from July 2009 through June 2013. Of the study population (n = 1217), 65% had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Research is now emerging that demonstrates EHRs’ potential for positive impact within coordinated care models. For example, Matiz and colleagues [ 33 ] found that enhancements to the EHR that added a care plan template were associated with a fourfold increase in care plan use. King and colleagues found that EHR use was associated with physicians’ adherence to research-based care coordination processes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research is now emerging that demonstrates EHRs’ potential for positive impact within coordinated care models. For example, Matiz and colleagues [ 33 ] found that enhancements to the EHR that added a care plan template were associated with a fourfold increase in care plan use. King and colleagues found that EHR use was associated with physicians’ adherence to research-based care coordination processes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, telephone‐based communication may not always be feasible and instead a streamlined electronic process and online forms can also be used effectively. In one study, such forms, physical or virtual, streamlined the process of care coordination and improved the workflow of care for patients 48 . Hamburger et al 46 also included the use of forms by way of medication administration care plans, and this study concluded that there were positive associations regarding the care provided.…”
Section: Resultsmentioning
confidence: 99%
“…When all members of the care team know what to do, the needs of the child and family can be appropriately addressed. For example, streamlining paperwork can ensure that there is a clear record of what the family needs and what services have already been provided 48 . This can make problem solving more effective in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One study developed a new electronic health record (EHR) for this purpose. 49 Two studies used individual EHR/electronic medical record (EMR) tools, 50,51 and 2 studies used online patient-centered tools. 52,53…”
Section: Resultsmentioning
confidence: 99%